-10z-(-9z)+(-4z)=10

Simple and best practice solution for -10z-(-9z)+(-4z)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10z-(-9z)+(-4z)=10 equation:



-10z-(-9z)+(-4z)=10
We move all terms to the left:
-10z-(-9z)+(-4z)-(10)=0
We get rid of parentheses
-10z+9z-4z-10=0
We add all the numbers together, and all the variables
-5z-10=0
We move all terms containing z to the left, all other terms to the right
-5z=10
z=10/-5
z=-2

See similar equations:

| 20k+3k-20k-2k+k=8 | | 23+3x=-76+12x | | 221.55b+20.95=85 | | 3x+4=-8+7x | | 15+7x-42-x=33-x-5+2x | | 3x+4=-8+7 | | 100=-9.8t^2-15t+100 | | 2(x+3)=8(x-2) | | 4(h-66)=100 | | D+7d+3=19 | | 5y-3-4y=5 | | x+8x=2.5 | | 9h-9h+5h-4h=17 | | 17y-17y+2y=16 | | 6x+7=43  | | 25-4p=1 | | 12y=36. | | 5p-14p-(-19p)-(-3p)-2p=-11 | | 5s-1=6s+6 | | 6=j/3-2 | | 3(x+2)+15=2x | | 1c+72=82 | | -8j+19=67 | | 5x-8=5x-12 | | 5x+5=3x+26 | | 15+3w=60 | | 2q-41=47 | | f/7+39=45 | | -3x+8(-7x-7)=7+4x | | 9c+17=71 | | 81/2+k=15 | | (3v-2)(3v-7)=0 |

Equations solver categories